A dimensional analysis of forest fuel layer ignition model: Application to the ignition of pine needle litters. (July 2015) - Lamorlette, Aymeric; Houssami, Mohamad El; Thomas, Jan C; Simeoni, Albert; Morvan, Dominique
This article deals with the physical modelling of forest fuel layer ignition. A model based on momentum-, fluid- and solid-phase energy equations is written for a fuel layer and a dimensional analysis is performed. This analysis allows to enlighten on two relevant dimensionless groups regarding the dimensionless time to ignition of a fuel layer and also provides a suited scaling for the fluid velocity inside the fuel layer during ignition. A correlation for the time to ignition is then fitted on experimental data obtained using an FM-Global fire propagation apparatus for different pine species with a closed basket. A good agreement is found, emphasizing the relevance of the dimensionless groups and the thermally thick behaviour of the solid particles during the ignition process under incident radiant heat flux as low as8 − 12 kW m − 2 .